Vibration response from the planetary gear with flexible ring gear - Xue, Song; Howard, Ian (2019)
This paper investigates the vibration response from the planetary gearbox with a flexible ring gear, supported by various constraints, resulting in quite different vibration spectra. The ring gear with its supports was modelled in ANSYS as a transient finite element moving load beam problem to formulate the vibration response. The moving load was represented by the dynamic gear mesh forces, which were obtained from a planetary gear lumped-parameter model. Two support conditions were analysed in this research. In the uniform support condition, it was found that the modulation effect from the carrier arm rotation can be accurately predicted and the vibration spectra matched well with previous publications. In the pin support condition, the spectra from different ring gear rim locations can result in different vibration spectra and it provides a primer guideline for further understanding the effect of the sensor location on the planetary gear vibration monitoring.